Pelatihan Keterampilan Penggunaan Alat Pakan Ikan Otomatis Berbasis Internet Of Things (IOT) - Fitrian, Andry; Astuti, Irnin Agustina Dwi; Yohanna, Larisa; Mubarok, Dzulfikri Ali; Taqwandi, Fattah Hafri (PUNDIMAS: Publikasi Kegiatan Abdimas, 2024)
Karang Taruna Kalideres Village has a fish pond for cultivating fish, especially catfish. However, there are obstacles for Karang Taruna members who take care of their ponds, namely the management time must be intensive to provide fish feed. Therefore, assistance and understanding are needed for partners in managing fish cultivation using automatic fish feeders based on the Internet of Things (IoT) so that they can be utilized properly by the community. The community service team provides socialization, counseling and training in the use of automatic fish feeders based on the Internet of Things (IoT) to partners. The methods used in community service are socialization, discussion, training, and assistance. The implementation of this Community Service was carried out from July to September 2023. There were 20 participants who took part in this activity. Based on the analysis of the questionnaire given to partners, there was an increase in partner understanding regarding the use of automatic fish feeders based on the Internet of Things (IoT) by 60%. Participants were very enthusiastic and excited about participating in this activity. Automatic feeder technology based on the Internet of Things (IoT) is one alternative solution to problems in fish farming efforts.